The effect of voltage and time of exposure on surface hardness of resin modified glass ionomer cement - Titien Hary Agustantina (Dental Journal (Majalah Kedokteran Gigi), 2007)
Light intensity can affect the polymerization of resin-based material therefore it will also affect surface hardness. To compensate reduction of light intensity becaused of the input of low voltage (200 and 210 volt), the exposure time was prolonged to be 40 and 60 seconds. The purpose of this study was to know the effect of voltage and time of exposure of resin modified glass ionomer cement on surface hardness. This study was completed with seventy two samples of resin modified glass ionomer cement 5 mm in diameter and 2 mm in height, exposed by visible light curing for 20, 40, and 60 seconds with voltage input 220, 210 and 200 volt. Micro vickers hardness tester was used to test surface hardness on the upper surface of sample. Two-way ANOVA test and Least Significant Difference (LSD) were used in data analysis with 5% level of significance. The result showed that lower input (210 and 210 volt) would decrease surface hardness of resin modified glass ionomer cement, longer exposure time (40 and 60 seconds) would increase the surface hardness of resin modified glass ionomer cement. The conclusion is the prolong of exposure time from 20 seconds to 40 and 60 seconds in all voltage input could increase surface hardness of resin modified glass ionomer cement.